Perspectives on the backsliding impact of Helsinki Accords on Romania’s human rights policies - POPA, Paul (Studia Universitatis Babeș-Bolyai Historia, 2025)
The Helsinki Accords and their human rights provisions have been seen as pivotal in fostering dissident networks and improving human rights in East-Central Europe. In Romania, the political culture was characterized by a focus on security over individual liberties. While the Helsinki Accords were intended to promote human rights and cooperation in Eastern Europe, their effect in Romania was counterproductive. The regime’s interpretation of the Accords allowed it to maintain a repressive stance, which, in turn, isolated the country internationally. The Romanian communist leadership viewed the Helsinki Accords primarily as a means to shield itself from external interference, entirely sidelining the human rights commitments outlined in the agreement. This interpretation allowed the communist regime to justify its oppressive policies while presenting a façade of compliance with international norms. As a result, rather than fostering positive change, the Accords contributed to Romania’s isolation on the international stage, particularly as the country became the only one in the Eastern Bloc to see a deterioration in human rights conditions post-signing. Rezumat: Acordurile de la Helsinki și dispozițiile lor privind drepturile omului au fost considerate esențiale în promovarea rețelelor dizidente și îmbunătățirea drepturilor omului în Europa Centrală-Est. În România, cultura politică s-a caracterizat printr-un accent pe securitate în detrimentul libertăților individuale. În timp ce Acordurile de la Helsinki au fost menite să promoveze drepturile omului și cooperarea în Europa de Est, efectul lor în România a fost contraproductiv. Interpretarea Acordurilor de către regim i-a permis să mențină o poziție represivă, care, la rândul său, a izolat țara pe plan internațional. Conducerea comunistă română a văzut Acordurile de la Helsinki în primul rând ca pe un mijloc de a se proteja de interferența externă, eliminând în totalitate angajamentele privind drepturile omului conturate în acord. Această interpretare a permis regimului comunist să-și justifice politicile opresive, prezentând în același timp o fațadă de conformitate cu normele internaționale. Drept urmare, mai degrabă decât să favorizeze schimbări pozitive, Acordurile au contribuit la izolarea României pe scena internațională, mai ales că țara a devenit singura din Blocul de Est în care s-a observat o deteriorare a condițiilor drepturilor omului după semnare. Cuvinte-cheie: drepturile omului, Acordurile Helsinki, politici de protecţie ale drepturilor omului